Seismic reflection data over Azores Plateau - Hübscher, Christian (PANGAEA, 2022)
This are composite seismic reflection data crossing the Azore Plateau. Data have been collected in 2016 during RV Meteor expedition M113/1. Two GI-Guns (45/105 cin; true GI-Mode) pops were recordeed by a digital streamer of 600 m length. For details see reference. Numbers in the file names refer to profiles as described in cruise report and Hübscher et al. (2018).
Keywords: M113/1; Seismic reflection data